2007
DOI: 10.1038/sj.mt.6300286
|View full text |Cite
|
Sign up to set email alerts
|

Immunization by Application of DNA Vaccine onto a Skin Area Wherein the Hair Follicles Have Been Induced into Anagen-onset Stage

Abstract: An attractive approach to immunization is to apply DNA vaccine topically onto the skin. However, it is important to ensure that a strong immune response is induced without disrupting the skin stratum corneum. The hair follicles have been shown to be the major portal of entry for DNA applied onto the skin, and it has been reported that the transfection of hair follicle cells occurs mainly at the onset of a new growing stage of the hair cycle. Using an anthrax protective antigen (PA) protein-encoding plasmid in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…14 At least for DNA vaccines the hair cycle state also seems to determine the successful transfection. 15 Inside the hair follicles antigen uptake by the rich pool of peri-follicular antigen presenting cells (APCs) is facilitated due to the absence of a SC barrier in the lower follicular orifice. 16 Therefore this delivery strategy very attractive for antigen encapsulation.…”
Section: Nanoparticles For Transfollicular Vaccinationmentioning
confidence: 99%
“…14 At least for DNA vaccines the hair cycle state also seems to determine the successful transfection. 15 Inside the hair follicles antigen uptake by the rich pool of peri-follicular antigen presenting cells (APCs) is facilitated due to the absence of a SC barrier in the lower follicular orifice. 16 Therefore this delivery strategy very attractive for antigen encapsulation.…”
Section: Nanoparticles For Transfollicular Vaccinationmentioning
confidence: 99%
“…5 However, TF vaccination is usually performed after pre-treating the skin area by plucking hairs, waxing or cyanoacrylate (superglue) stripping. [6][7][8] Pre-treatment not only permeabilizes the skin by removing the upper layers of the SC, but also activates the innate immune system. 1 While both factors probably improve the immunogenicity of a topically applied vaccine, the disadvantage of the method is that permeabilization of the skin increases considerably the risk of infections.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al (1999) reported that functional hair follicles were required for a topically applied DNA vaccine to induce immune responses [11]. Based on the aforementioned findings, we hypothesized, and provided data to support, that transcutaneous immunization by applying plasmid DNA onto a skin area wherein the hair follicles were induced into growth stage by hair plucking elicited a stronger antibody response than when the hair follicles in the application area were in the resting stage [15]. …”
Section: Introductionmentioning
confidence: 86%
“…The levels of anti-PA and anti-gp160 in serum samples were determined using ELISA [15]. Briefly, EIA/RIA flat bottom, medium binding, polystyrene, 96-well plates (Corning-Costar, Corning, NY) were coated with 100 ng of PA (List Biological) or the gp140 protein (NIH AIDS Research & Reference Reagent Program) dissolved in 100 µL carbonated buffer (0.1 M, pH 9.6) at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation